Pengaruh Capital Expenditure dan Cash Holding terhadap Perataaan Laba - Rahmaniar, Rahmaniar (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2023)
This study aimed to determine the effect of capital expenditure and cash holding on earnings smoothing in manufacturing companies listed on the Indonesia Stock Exchange know 2016 to 2021. The data analysis method in this study uses multiple linear regression to predict the effect of independent variables. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2021. The sampling method in this study was the purposive sampling method. The results showed that capital expenditure affects earnings smoothing. This proves that adding fixed assets, as capital expenditure indicates, increases profits. Suppose the increase in capital expenditure will increase the profit level significantly. Cash holding affects earnings smoothing. This proves that the higher the cash holding or, the higher the cash in the company, the higher the earnings smoothing.